Медіаграмотність та емоційна стійкість населення України у контексті протидії російській агресії - Юрій, Аліна Олександрівна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
This report aims to study the theoretical essence and peculiarities of the interaction between the development of media literacy in Ukrainian society and countering Russian disinformation. The role of the media in the restoration of a traumatized society was considered. A theoretical basis was also determined to confirm the effective use of the media literacy development tool at the state level for the formation of the post-war security system in Ukraine.